(untitled) (Gestão & Regionalidade, 2018)
This research aims to identify the existence of a hierarchy on the relationship between a focal company and its suppliers. The study is defined as a descriptive research, which adopted as research strategy a survey using a structured questionnaire with closed questions. The sample was a convenience sample composed by 25 companies, one of them being the focal company. Cluster analysis found four different partnership profiles, based on drivers and facilitators variables. It was possible to describe the profile of each group of suppliers and, remarkably, a trend to hierarchy of the partnerships between the focal company and its suppliers. The group of companies with more interaction is characterized by having long-term contracts and greater mutual interest in profit sharing process, but the risk tolerance proved identical to the other companies. Keywords: Supply chain; partnerships; customer-supplier relationship; governance.